2008
DOI: 10.1063/1.2970162
|View full text |Cite
|
Sign up to set email alerts
|

Direct structural evidence of the change in N-III bonding in (GaIn)(NAs) before and after thermal annealing

Abstract: The blueshift of the fundamental energy gap of ͑GaIn͒͑NAs͒ upon thermal treatment is well established. However, the physical reason is still controversially discussed in literature. In the present paper we give direct structural evidence using transmission electron microscopy in combination with structure factor calculation that this blueshift-for the metal organic vapor phase epitaxy grown samples investigated here-results solely from a change in the local environment of nitrogen. N is bound to Ga upon growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Keating potentials were calculated based on the lattice constants and elastic constants in Table 1. It was shown by Müller et al (2010), Müller et al (2011), and Volz et al (2008) that the VFF relaxation is an adequate approach to consider the scattering at SADs in conventional TEM simulations of InGaNAs.…”
Section: Reference: Haadf Intensitymentioning
confidence: 99%
“…Keating potentials were calculated based on the lattice constants and elastic constants in Table 1. It was shown by Müller et al (2010), Müller et al (2011), and Volz et al (2008) that the VFF relaxation is an adequate approach to consider the scattering at SADs in conventional TEM simulations of InGaNAs.…”
Section: Reference: Haadf Intensitymentioning
confidence: 99%
“…We were also able to show this change in the nitrogen environment upon annealing by dark field TEM recently. 21 As these results have important implications on the performance of devices which use Ga͑NAs͒ as barrier material together with ͑GaIn͒͑NAs͒ as active material, we are currently investigating annealing conditions, which result in an improvement of material quality for the quaternary alloy without deteriorating the ternary Ga͑NAs͒ barrier material.…”
Section: Resultsmentioning
confidence: 99%
“…As there are no indications of indium diffusion after annealing, this does not seem to occur. The indium concentration decrease can be explained by an increasing number of In-N bonds, leading to a change of the 200 structure factors [8], and hence to a misassignment of the concentrations. A growing number of In-N bonds is also plausible because it minimizes the strain energy of the crystal [7] and it is discussed as a reason for the blueshift after thermal annealing [5].…”
Section: Discussionmentioning
confidence: 99%
“…To explain the blueshift of In x Ga 1-x N y As 1-y during annealing, structural properties were investigated. Some authors found evidence for an increase of preferred indiumnitrogen bonding [5,7,8], while others found evidence for long-range redistribution of nitrogen or indium [6,9]. So there might be different mechanisms contributing to the band gap increase.…”
Section: Introductionmentioning
confidence: 99%